Modeling of light propagation and molecules alignment in nematic liquid crystals of planar orientation - Sala, Filip; Karpierz, Mirosław A (Photonics Letters of Poland, 2012)
In this work results of light propagation in nematic liquid crystals of planar orientation are presented. For calculations fully vectorial Beam Propagation Method combined with model describing molecules orientation is used. We focus on a comparison between one- and two-angle model describing director orientation. Differences in light propagation and polarization of the propagated beams are also shown. Full Text: PDF References: U.A. Laudyn, M. Kwasny, M.A. Karpierz, "Nematicons in chiral nematic liquid crystals", Appl. Phys. Lett. 94, 091110 (2009).CrossRef U.A. Laudyn, M. Kwaśny, K. Jaworowicz, K.A. Rutkowska, M.A. Karpierz, G. Assanto, "Properties of spatial solitons in chiral nematic liquid crystal cells", Photon. Lett. Poland 1, 7 (2009).CrossRef G. Assanto, M.A. Karpierz, "Nematicons: self-localised beams in nematic liquid crystals", Liq. Cryst. 36, 1161 (2009).CrossRef G. Assanto, M. Peccianti, C. Conti, "Nematicons: Optical Spatial Solitons in Nematic Liquid Crystals", Opt. Photon. News 14, 44 (2003).CrossRef G.D. Ziogos, E.E. Kriezis, "Modeling light propagation in liquid crystal devices with a 3-D full-vector finite-element beam propagation method", Opt. Quant. Electron 40, 10 (2008).CrossRef F.A. Sala, M.A. Karpierz, "Numerical simulation of beam propagation in a layer filled with chiral nematic liquid crystals", Photon. Lett. Poland 1, 163 (2009).CrossRef I-C Khoo, Liquid crystals (John Wiley & Sons, Inc 2007).CrossRef